COMPENSATION FOR WRONGFUL CONVICTION IN SOUTH AFRICA - Jamil Ddamulira Mujuzi (Obiter, 2023)
South Africa acceded to the International Covenant on Civil and Political Rights (ICCPR) without reservations. Article 14(6) of this treaty requires South Africa to put measures in place to compensate people who have suffered miscarriages of justice (wrongful convictions). However, the right to be compensated for wrongful conviction is not provided for in South African law. This is so although case law shows that many people have been wrongfully convicted. A person who has been wrongfully convicted has to institute a civil case (delictual claim) or to apply for a free pardon. In this article, the author argues that these two options do not comply with what is required of South Africa under article 14(6) of the ICCPR. The author suggests ways in which South Africa could comply with its obligation under article 14(6) of the ICCPR. The author also suggests ways in which the common law (actio iniuriarum) could be developed to compensate people who have been wrongfully convicted.